Problems and snapshots from the world of probability - Blom, Gunnar 1930-; Holst, Lars; Sandell, Dennis (Springer, 1994)
A wide range of readers will enjoy this diverse selection of topics. Students will find this a helpful and stimulating companion to their probability courses. The snapshots will leave the students with an expanded knowledge about topics not generally covered by textbooks. Other than a basic exposure to probabilistic ideas, such as might be gained from a first course in probability, it is self-contained